Gross and microscopic anatomy of the nasal cavity, including olfactory epithelium, of the florida manatee (Trichechus manatus latirostris) - Barboza, Meghan L. B.; Larkin, Iskande L.V. (Aquatic Mammals, 2020)
As a fully aquatic mammal, the Florida manatee (Trichechus manatus latirostris) spends a limited amount of time at the water's surface. However, as a mammal that breathes air, they do need to filter, warm, and humidify that air, and anecdotal evidence indicates manatees have a sense of smell. This study characterized the nasal turbinate system, including identification of the olfactory epithelium, and compared it to other mammals using a combination of gross and micro-anatomic examination. Major turbinates were present, including nasal, maxillary, and ethmoturbinates, but with minimal convolution. The respiratory epithelium was found throughout much of the nasal cavity and covered maxillary and nasal turbinates, as well as the septum. Mucus-producing cells and cavernous veins were extensive. The olfactory epithelium was found in the dorsocaudal ethmoturbinates. As a herbivore that feeds predominantly underwater, the manatee likely relies on taste and touch for assessing food and, therefore, does not need to use smell in the same way as other marine mammals such as mysticetes (Bouchard et al., 2019) and pinnipeds (Kowalewsky et al., 2006). However, there are still substantial numbers of olfactory cells, especially considering the decreased amount of exposure time to odorants when breathing at the surface. Therefore, the question remains of why manatees have maintained their ability to smell while other fully aquatic species such as odontocetes have not. Future research should focus on a combination of behavioral and molecular techniques to fully understand the olfactory capabilities of the Florida manatee. © 2020, European Association for Aquatic Mammals.
Keywords: Anatomy; Chemoreception; Mammalia; Manatee; Nasal; Olfaction; Pinnipedia; Trichechidae; Trichechus manatus; Trichechus manatus latirostris; anatomy; comparative study; dept.bio; herbivore; olfaction; peer-reviewed; sirenian